Tips and traps for getting started as a real estate agent - Irwin, Robert (McGraw-Hill, 2007)
This book includes: Manage your time for maximum efficiency; Work less and earn more by closing bigger deals; Bring in more referrals so you can stop hunting for clients; Take home a bigger commission in every deal.